Thirty-Year Mortality After Coronary Artery Bypass Graft Surgery: A Danish Nationwide Population-Based Cohort Study. Issue 5 (May 2017) - Adelborg, Kasper; Horváth-Puhó, Erzsébet; Schmidt, Morten; Munch, Troels; Pedersen, Lars; Nielsen, Per Hostrup; Bøtker, Hans Erik; Toft Sørensen, Henrik
Abstract : Background—: Data are sparse on long-term mortality after coronary artery bypass graft (CABG) surgery. We examined short-term and long-term mortality of patients undergoing CABG surgery and a general population comparison cohort. Methods and Results—: Linking data from Danish registries, we conducted a nationwide, population-based cohort study on 51 307 CABG patients and 513 070 individuals from the general population matched on age, sex, and calendar year (1980–2009). The mortality risk was higher in patients having isolated CABG surgery than in the general population, particularly during 0 to 30 days (3.2% versus 0.2%), 11 to 20 years (51.1% versus 35.6%), and 21 to 30 years (62.4% versus 44.8%), but not substantially higher during 31 to 364 days (2.9% versus 2.4%) or 1 to 10 years (30.7% versus 25.8%). The 30-day adjusted mortality rate ratio for isolated CABG surgery was 13.51 (95% confidence interval [CI], 12.59–14.49). Between 31 to 364 days and 1 to 10 years, the isolated CABG surgery cohort had a slightly higher mortality rate than the general population comparison cohort, adjusted mortality rate ratios of 1.15 (95% CI, 1.09–1.21) and 1.09 (95% CI, 1.08–1.11), respectively. Between 11 to 20 years and 21 to 30 years, the adjusted mortality rate ratios were 1.62 (95% CI, 1.58–1.66) and 1.76 (95% CI, 1.62–1.91). Within 30 days, CABG patients had a 25-fold, a 26-fold, and a 18-fold higher risk of dying from myocardial infarction, heart failure, or stroke, respectively, than members of the general population comparison cohort. We found substantial heterogeneity in absolute mortality rates according to baseline risk groups. Conclusions—: The isolated CABG cohort had a higher mortality rate than the general population comparison cohort, especially within 30 days of and 10 years after surgery. Abstract : Supplemental Digital Content is available in the text.